2009
DOI: 10.1366/000370209789806867
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Uranium Using Laser-Induced Breakdown Spectroscopy

Abstract: The goal of this work is a detailed study of uranium detection by laser-induced breakdown spectroscopy (LIBS) for application to activities associated with environmental surveillance and detecting weapons of mass destruction (WMD). The study was used to assist development of LIBS instruments for standoff detection of bulk radiological and nuclear materials and these materials distributed as contaminants on surfaces. Uranium spectra were analyzed under a variety of different conditions at room pressure, reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…Argon was chosen as the ambient gas due to its inert properties; a reactive ambient gas such as air could affect plasma emission properties due to quenching; 17 moreover, uranium is oxygen-reactive, causing increased background emission in the presence of air. 13 Table I lists the U I lines identified in the analyzed emission region (350 nm to 370 nm, chosen due to the absence of interference from matrix emission lines) and their spectroscopic parameters, obtained from Ref. 18; the U I 356.18 nm line was used for studying analytical merits of spectral emission and OTOF studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Argon was chosen as the ambient gas due to its inert properties; a reactive ambient gas such as air could affect plasma emission properties due to quenching; 17 moreover, uranium is oxygen-reactive, causing increased background emission in the presence of air. 13 Table I lists the U I lines identified in the analyzed emission region (350 nm to 370 nm, chosen due to the absence of interference from matrix emission lines) and their spectroscopic parameters, obtained from Ref. 18; the U I 356.18 nm line was used for studying analytical merits of spectral emission and OTOF studies.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, uranium's multi-electron system means that the spectral line emission is very crowded, with significant line overlapping. Chinni et al 13 attributed increased background emission to overlapping of the high density U lines and observed that the background decays with the same behavior as both neutral and ionic line emission, indicating that the background emission is increased by line emission itself. However, our OTOF studies showed that (given in Sec.…”
Section: A Laser Excitation Energy Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chinni et al, [7] the presence of strong background emission seen in U plasmas could be due to overlapping of high density U lines.…”
Section: Resultsmentioning
confidence: 94%
“…LA-Laser Absorption Spectroscopy (LA-LAS) is an extremely sensitive method capable of probing elemental as well as isotopic ground and excited state populations [4,5]. LA -Optical Emission Spectroscopy (LA-OES), commonly called Laser Induced Plasma Spectroscopy (LIPS) or Laser Induced Breakdown Spectroscopy (LIBS), provides another dimension to LA-hyphenated techniques in nuclear forensics where light emission from the plasma plume is analyzed [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%